The influence of language of advertising on customer patronage intention: testing moderation effects of race - Rahman, Muhammad Sabbir; AbdelFattah, Fadi AbdelMuniem; Mat Daud, Nuraihan; Osman, Mohamad (IDOSI Publications, 2014)
The purpose of this paper is to examine how the language of advertising (LA) influences customer patronage intention (CPI) towards health insurance products in Malaysia. The research also considers the moderating effects of race between LA and CPI. In order to test the hypothesized model, this study uses the responses from a sample of 160 customers of different health insurance service providers in Malaysia. A questionnaire was formed using the required measures from existing literature and the structural equation modeling (SEM) was used to examine the proposed model. The results show that the moderating effects of race were strong between languages of advertising and customer patronage intention. The result also displays a significantly positive relation between advertising languages and customer patronage intention towards health insurance products in Malaysia. The researchers suggest that a coherent and persuasive advertising language be used by health insurance providers.